The Role of Financial Constraints in The ESG Performance and Financial Performance Relationship - Renny Wulandari; Rina Mayasafitri; Febriati Febriati (Jurnal Akuntansi, 2026)
Purpose – This study is to determine the influence of ESG performance on a financial performance, considering financial constraints encountered by the company. Design/Methodology/Approach – Using a sample of businesses listed on the Indonesian Stock Exchange between 2017 and 2023, regression with moderate regression analysis is the methodology employed. Findings – The results of the study prove that a company's ESG performance can increase its profitability and that financial constraints do not influence or moderate the effect of ESG performance on financial performance. Research limitations/Implications – The Financial Services Authority (OJK) and the IDX can evaluate whether the sustainability reporting mandate places an additional burden on financially constrained companies or whether it can actually help companies gain access to green financing. The results of this study can be used as a preliminary reference in formulating a more targeted incentive scheme for companies committed to ESG, especially for companies with financial constraints. Keywords: ESG Performance, Financial Constraint, Financial Performance, Indonesia, Sustainability